Prediction of Persistent Storage Symptoms after Transurethral Resection of Prostate in Patients with Benign Enlargement of Prostate (Bangladesh Journal of Urology, 2022)
Introduction: Benign enlargement of prostate (BEP) is one of the common problem in elderly male. Most of the patients present with lower urinary tract symptoms (LUTS) which consist of voiding symptoms and storage symptoms. Transurethral resection of prostate (TURP) is the gold standard treatment option for BEP. TURP improves both obstructive and storage symptoms in majority of cases. But sometimes storage symptoms persist after TURP. This study was done to predict the factors for persistence of storage symptoms after TURP by evaluating clinical and urodynamic variables.Objective: To predict the factors for persistence of storage symptoms after transurethral resection of prostate (TURP) by evaluating clinical and urodynamic variables.Materials and Method: This was a prospective analytic study done in the department of Urology, Bangabandhu Sheikh Mujib medical university (BSMMU), Shabagh, Dhaka. In this study, total 60 patients of BEP with the indication of TURP were enrolled. Preoperative data includes Age of the patient, International prostate symptoms score(IPSS), IPSS storage sub score, Qmax, QoL scores, Maximum cystometric capacity(MCC), Post void residue(PVR), PdetQmax, Bladder contractility index (BCI) and postoperative data includes post-operative IPSS storage sub score, Qmax were recorded and analyzed.Result: Among preoperative variables, Age (>65y) and IPSS storage sub score has highest predictive value. Bladder contractility index (BCI) and MCC have significant predictive value. Qmax and PVR have also predictive value.Conclusion: This study result shows elderly patient of higher age group, preoperative high IPSS storage sub score, smaller MCC & high BCI have chance of persistence of storage symptoms.Bangladesh J. Urol. 2021; 24(2): 135-140